Carcinoma of the Ectopic Breast (Journal of Enam Medical College, 2013)
A 43-year-old woman presented with bilateral ectopic breasts in both the axillae in Chittagong Medical College Hospital in July 1996. She was diagnosed having carcinoma in the left ectopic breast. She was successfully treated with local surgical excision and regional lymph node dissection, adjuvant chemotherapy, loco-regional radiotherapy and hormone therapy. The patient continued tamoxifen for 5 years. Till last follow-up in December 2011, the patient was asymptomatic without any evidence of residual disease or local recurrence and evidence of metastases. DOI: http://dx.doi.org/10.3329/jemc.v3i1.13874 J Enam Med Col 2013; 3(1): 47-49